Analysis of the Effect of Frugal Living on Employee Financial Management in Achieving Financial Freedom - Hartantri, Rizki; Setyadi, Bakti; Gunarto, Muji (International Journal of Finance Research, 2024)
Employees are advised to apply the concept of frugal living or save at all costs to break the chain of debt that could endanger their financial condition. Employees may achieve financial freedom more quickly by practicing frugal living from an early age and managing finances well. Planning for financial freedom is essential because one day, people will lose their ability to work. This research collected data from 150 employee respondents who worked in private or civil agencies. The uniqueness of this research lies in the data processing method; it is known that the t-test value for the frugal living variable has a value of 56,85, which is greater than the t-table of 1.66. This means that the research results show that the Frugal Living lifestyle significantly affects employee financial management. In contrast, the relationship between financial management and financial freedom has no significant effect. Apart from that, the relationship between Frugal Living and financial freedom also does not have a significant effect. This research contributes to increasing insight for employees to implement the Frugal Living lifestyle in achieving financial freedom at an early age